Corrosion and Electrochemical Properties of Nanocrystalline W-Mo Alloys in NaOH Solutions - Khadka, Arun; Bhattarai, Jagadeesh (Nepal Journal of Science and Technology, 2011)
The corrosion and electrochemical properties of sputter-deposited nanocrystalline binary W-Mo alloys were studied after immersion for 2429 h in different concentrations of NaOH solutions open to air at 25°C using corrosion tests and open circuit potential measurements. Molybdenum acts synergistically with tungsten in enhancing the corrosion resistance of the sputter-deposited binary W-Mo alloys so as to show higher corrosion resistance than those of alloy-constituting elements (i.e. tungsten and molybdenum) after immersion for 24 h in NaOH solutions. Open circuit potentials of all the examined sputter-deposited W-Mo alloys are shifted to the more positive (noble) direction with increasing molybdenum content in the alloys. The stability of the spontaneously passivated films formed on the binary W-Mo alloys is decreased with increasing concentrations of NaOH solutions. In spite of these facts, the corrosion rates of all the examined W-Mo alloys are almost independent of concentrations of NaOH solutions after immersion for 24 h at 25°C. Key words: nanocrystalline W-Mo alloys; sputter deposition; corrosion resistance; open circuit potential; NaOH solutions DOI: 10.3126/njst.v11i0.4137 Nepal Journal of Science and Technology 11 (2010) 147-152